Partners in prosperity : the changing geography of the transatlantic economy - Hamilton, Daniel S.; Quinlan, Joseph P. (Washington, DC : Center for Transatlantic Relations, 2004)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: handel; economische aardrijkskunde; Europese Unie (EU).; Verenigde Staten van Amerika